Catalytic Co-Pyrolysis Of Sugarcane Bagasse And Waste Plastics Using Zeolite And Hydroxyapatite Based Catalyst For High Quality Pyrolysis Oil In A Fixed-Bed Reactor - Hassan, Hamizura (2019)
Depletion of natural resources, massive demand for petroleum, and environmental concern have motivated studies on renewable fuel from biomass conversion. This study aims to investigate the co-pyrolysis and catalytic co-pyrolysis of sugarcane bagasse (SCB) with high-density polyethylene (HDPE) or polyethylene terephthalate (PET) in a slow-heating fixed-bed reactor over faujasite type zeolite (FAU-EAFS) and hydroxyapatite-zeolite (HAP-ZE) catalysts prepared from electric arc furnace slag. In co-pyrolysis process, the effects of reaction temperature (400-700 ℃) and biomass-to-plastic ratio (100:0-0:100) on the products yields, chemical compositions as well as synergistic effect were investigated. The optimum liquid yield of 63.69 wt% was achieved at 600 °C and 60:40 SCB: HDPE ratio in co-pyrolysis of SCB and HDPE while 60.94 wt% of liquid yield was achieved at 600 °C and 40:60 SCB: PET ratio in co-pyrolysis of SCB and PET. In catalytic co-pyrolysis section, the effects of reaction temperature (400-700 ℃), catalyst-to-feedstock ratio (1:10-1:2) and biomass-to-plastic ratio (100:0-0:100) on the product yields and chemical compositions were investigated. The maximum pyrolysis oil yield of 68.56 wt% and 71.01 wt% were obtained under catalytic co-pyrolysis of SCB and HDPE over FAU-EAFS and HAP-ZE, respectively. The catalytic co-pyrolysis of SCB and PET over FAU-EAFS and HAP-ZE, produced maximum pyrolysis oil yield of 42.95 wt% and 45.64 wt%, respectively. The catalytic co-pyrolysis of SCB and HDPE promoted the production of hydrocarbon and alcohol while the catalytic co-pyrolysis of SCB and PET enhanced the aromatic and acid production. Compared to HAP-ZE, the FAU-EAFS showed better performance in the production of hydrocarbon and aromatic during catalytic co-pyrolysis of SCB with HDPE or PET, due to its strong acidity and larger pore size which enhanced cracking and deoxygenation reactions and diffusion efficiency of pyrolysis vapors into the catalyst pore. Thermal pyrolysis, co-pyrolysis and catalytic co-pyrolysis behaviour of SCB and HDPE were determined using thermogravimetric analysis while the kinetic parameters were calculated via Coats-Redfern method. In the second region, where the decomposition of cellulose and hemicellulose are dominant, the best correlation for HDPE can be described by first order chemical reaction mechanism, whereas the other reaction samples are controlled by diffusion model. Meanwhile, in the third region, where the interaction between SCB and HDPE took place, all of the reactions samples followed the order of reaction mechanisms. An addition of FAU-EAFS and HAP-ZE catalysts resulted in lower activation energy in the second region during co-pyrolysis of SCB and HDPE.